Cancer Chemotherapy: Redox‐Responsive Dual Drug Delivery Nanosystem Suppresses Cancer Repopulation by Abrogating Doxorubicin‐Promoted Cancer Stemness, Metastasis, and Drug Resistance (Adv. Sci. 7/2019). Issue 7 (3rd April 2019) - Liu, Jia; Chang, Bingcheng; Li, Qilin; Xu, Luming; Liu, Xingxin; Wang, Guobin; Wang, Zheng; Wang, Lin
Abstract : Chemotherapy effectiveness is greatly challenged by chemodrugs' intrinsic pathological interactions with tumor cells, which enhance cancer stemness, invasiveness and acquired drug resistance. In article number 1801987, Guobin Wang, Zheng Wang, Lin Wang, and co‐workers construct a redox‐responsive, celecoxib‐modified nanosystem that efficiently enhances doxorubicin‐based chemotherapy and suppresses cancer repopulation by abrogating doxorubicin‐induced enhancement of cancer stemness, metastasis and drug resistance.